Any other family eaudiobook - Brown, Eleanor (Penguin Audio, 2022)
A New York Times Book Review Editors' Choice The New York Times bestselling author of The Weird Sisters returns with a striking and intimate new novel about three very different adoptive mothers who face the impossible question: What makes a family? Though they look like any other family, they aren’t one—not quite. They are three sets of parents who find themselves intertwined after adopting four biological siblings, having committed to keeping the children as connected as possible. At the heart of the family, the adoptive mothers grapple to define themselves and their new roles. Tabitha, who adopted the twins, crowns herself planner of the group, responsible for endless playdates and holidays, determined to create a perfect happy family. Quiet and steady Ginger, single mother to the eldest daughter, is wary of the way these complicated not-fully-family relationships test her long held boundaries. And Elizabeth, still reeling from rounds of failed IVF, is terrified that her unhappiness after adopting a newborn means she was not meant to be a mother at all. As they set out on their first family vacation, all three are pushed into uncomfortably close quarters. And when they receive a call from their children’s birth mother announcing she is pregnant again, the delicate bonds the women are struggling to form threaten to collapse as they each must consider how a family is found and formed.